Clinical Effects and Antivenom Dosing in Brown Snake (Pseudonaja spp.) Envenoming — Australian Snakebite Project (ASP-14) - Allen, George E.; Brown, Simon G. A.; Buckley, Nicholas A.; O’Leary, Margaret A.; Page, Colin B.; Currie, Bart J.; White, Julian; Isbister, Geoffrey K. (PLOS ONE, 2012)
Background Snakebite is a global health issue and treatment with antivenom continues to be problematic. Brown snakes (genus Pseudonaja) are the most medically important group of Australian snakes and there is controversy over the dose of brown snake antivenom. We aimed to investigate the clinical and laboratory features of definite brown snake (Pseudonaja spp.) envenoming, and determine the dose of antivenom required. Methods and Finding This was a prospective observational study of definite brown snake envenoming from the Australian Snakebite Project (ASP) based on snake identification or specific enzyme immunoassay for Pseudonaja venom. From January 2004 to January 2012 there were 149 definite brown snake bites [median age 42y (2–81y); 100 males]. Systemic envenoming occurred in 136 (88%) cases. All envenomed patients developed venom induced consumption coagulopathy (VICC), with complete VICC in 109 (80%) and partial VICC in 27 (20%). Systemic symptoms occurred in 61 (45%) and mild neurotoxicity in 2 (1%). Myotoxicity did not occur. Severe envenoming occurred in 51 patients (38%) and was characterised by collapse or hypotension (37), thrombotic microangiopathy (15), major haemorrhage (5), cardiac arrest (7) and death (6). The median peak venom concentration in 118 envenomed patients was 1.6 ng/mL (Range: 0.15–210 ng/mL). The median initial antivenom dose was 2 vials (Range: 1–40) in 128 patients receiving antivenom. There was no difference in INR recovery or clinical outcome between patients receiving one or more than one vial of antivenom. Free venom was not detected in 112/115 patients post-antivenom with only low concentrations (0.4 to 0.9 ng/ml) in three patients. Conclusions Envenoming by brown snakes causes VICC and over a third of patients had serious complications including major haemorrhage, collapse and microangiopathy. The results of this study support accumulating evidence that giving more than one vial of antivenom is unnecessary in brown snake envenoming.